EVALUATION OF KNOWLEDGE AND BEHAVIOR ON ANALGESIC SELF-MEDICATION IN HEALTH AND NON-HEALTH STUDENTS AT MUHAMMADIYAH UNIVERSITY, YOGYAKARTA - Putri, Claryza Amelia; Rahajeng, Bangunawati (Jurnal Farmasi Sains dan Praktis, 2024)
Pain is the most common cause that encourages someone to do self-medication. A person's level of knowledge is known to influence a person's behavior in self-medication. The study evaluates the level of knowledge and behavior toward self-medication using analgesics among health and non-health students at the University of Muhammadiyah Yogyakarta. This research uses a non-experimental observational research design with a cross-sectional approach. The sample used was 752 health and non-health students at the University of Muhammadiyah Yogyakarta. The level of knowledge of health students is good, with a percentage of 75.3% good; 21.0% is sufficient; and 3.7% is less, while the level of knowledge of non-health students is adequate, with a percentage of 33.5% good; 50.5% is sufficient; and 16.0% is less. The behavior of health students is good, with 86.7% good, 12.5% adequate, and 0.8% less, while the behavior of non-health students is good, with 80.9% good, 17.5% enough, and 1.6% less. The difference in the level of knowledge and behavior of analgesic self-medication between health and non-health students is quite significant, with the results of the Mann-Whitney test analysis showing a value of 0.000 on the level of knowledge and 0.001 on behavior. The relationship between the level of knowledge and behavior of health students and the Spearman Rank correlation test showed a result of 0.039 with an R-value of 0.107. In contrast, non-health students showed a result of 0.027 with an R-value of 0.114, indicating a significant and weak relationship between both.